Análise de resultados do programa Ronda No Bairro na cidade de Manaus no ano de 2012 - Seffair, André Virgílio Belota (2014)
The analysis of results of public security policy is critical to the effectiveness of policies made by crime prevention and combating violence, constituting an important mechanism to project strategies and skillful routines for the achievement of objectives pursued by public policy adopted. In the State of Amazonas, adopted the Program Ronda no Bairro as an institutional policy of public security from the year 2012, taking the strategies of this policy been implemented throughout the urban area of Manaus. This work studies the results obtained from the implementation of the Program Ronda no Bairro in the administrative areas of the City of Manaus, in 2012, carrying out comparative analysis of the number of occurrences of the ten natures most relevant criminal offenses, recommended by the National Secretariat of Public Security – SENASP, checking the degree of efficiency of policing cycle, the dynamics of arrests, and the behavior of the numbers about prison population for the city of Manaus. The goal is to determine which elements had positive or negative results from the implementation of the Program.